THE ROLE OF SOCIAL ENTREPRENEURSHIP IN THE INTERACTION OF THE STATE AND SOCIETY - GONYUKOVA, Liliya (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines the role of social entrepreneurship in civil society in modern Ukraine. The purpose of the article was to identify the role of social entrepreneurship in the interaction of the state and society and to determine the ways of development of social entrepreneurship in Ukraine.The impact of social entrepreneurship on society is analyzed, and its role in solving social problems is determined. The need for developing relations between the state and society through the prism of social entrepreneurship is proven, and the main ways of improving the corresponding interaction are proposed. The ways of developing social entrepreneurship in Ukraine are proposed. It was established that in modern conditions, there needs to be a sufficient level of development of social entrepreneurship in Ukraine, which, in the presence of interaction between society and representatives of the authorities, can become a tool for solving social problems. It is emphasized that the connection between social entrepreneurship and public administration is dynamic and constantly developing.It has been proven that in today's conditions, the connection between social entrepreneurship and public administration is becoming stronger and stronger. This is explained by shared goals for promoting social and economic development, solving social problems, and increasing well-being.It was determined that in modern conditions, mechanisms of interaction between the state and society in the field of social entrepreneurship could take the following forms: financing of activities (individual projects); tax benefits, informational and advisory support; creation of a favorable business environment; establishment of partnership relations; social responsibility of business providing social services (products).
Keywords: Public management; management of social development; social entrepreneurship; socially responsible business; civil society; social sphere; ways of solving problems